2020
DOI: 10.2106/jbjs.oa.19.00068
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Osteoarthritis After Curettage and Calcium Phosphate Cementing for Giant-Cell Tumor of Bone Around the Knee Joint

Abstract: Background: Giant-cell tumor of bone (GCTB) is a locally aggressive intermediate bone tumor with a rarely metastasizing disposition. Standard surgical treatment consists of curettage, adjuvant treatment, and augmentation with allograft, autograft, or synthetics. Polymethylmethacrylate (PMMA) has been widely used for augmentation of the bone defect; however, the hyperthermic polymerization of PMMA may cause damage to articular cartilage, and the stiffness of the material may decrease the ability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 44 publications
0
22
0
3
Order By: Relevance
“…14 Araki et al reported strong functional outcomes despite presence of OA, with an average MSTS score of 29 points. 16 Although only reporting on five patients, Kito et al showed excellent function and minimal joint pain at mean follow-up of 28.1 years following distal femur GCTB curettage with PMMA. 17 In the current study, the mean postoperative MSTS score at latest follow-up was 25.1 compared with a score of 14.9 on initial presentation, confirming the functional benefit of surgical treatment of GCTB.…”
Section: Discussionmentioning
confidence: 96%
“…14 Araki et al reported strong functional outcomes despite presence of OA, with an average MSTS score of 29 points. 16 Although only reporting on five patients, Kito et al showed excellent function and minimal joint pain at mean follow-up of 28.1 years following distal femur GCTB curettage with PMMA. 17 In the current study, the mean postoperative MSTS score at latest follow-up was 25.1 compared with a score of 14.9 on initial presentation, confirming the functional benefit of surgical treatment of GCTB.…”
Section: Discussionmentioning
confidence: 96%
“…27 While some studies have found an increased risk of joint degeneration with the use of cement, [27][28][29] others have failed to find such association. [30][31][32] This difference has been attributed to the quantity of subchondral bone left after curettage: if the tumour is located less than 3 mm from the joint cartilage, the rate of joint degeneration increases significantly. For this reason, Benevenia et al 28 suggested the use of sheet subchondral bone graft as an adjunct to cement augmentation to reduce the rate of postoperative arthritis in the epiphysis of a long bone.…”
Section: Discussionmentioning
confidence: 99%
“…Araki et al conduziram o estudo de acompanhamento mais longo de avaliação do desenvolvimento de osteoartrite e a relataram em 26% dos pacientes após curetagem e cimentação. 29…”
Section: Discussionunclassified